The Effect Of Compliance Clinical Pathway On The Quality Of Service, Cost Of Treatment, Length Of Stay At Linggajati Hospital - Roheman, Roheman; Arrozi, M.F.; Dewi, Sandra (Teewan Journal Solutions, 2025)
Background: Good clinical governance in hospitals can be achieved by implementing clinical pathways. Compliance with the implementation of the inguinal hernia clinical pathway does not meet the minimum standard of 80%, for service quality it is at least 80%, for treatment costs it does not meet the INA CBGs standard for treatment class and the standard for length of stay does not meet the standard of ≤3 days. Objectives: This study aims to analyze the effect of compliance with the implementation of the inguinal hernia clinical pathway on service quality, treatment costs and length of stay at Linggajati hospital.Methods: This type of research is survey research. The population of this study was the medical records of inguinal hernia patients from January 2023-June 2024. The sample in this study was 204 respondents taken using purposive sampling technique. Univariate data analysis uses frequency distribution and the Three Box Method and multivariate analysis uses Multinomial Regression and Ordinary Least Square (OLS) Regression. Results: Compliance with the implementation of the inguinal hernia clinical pathway does not have an impact on the quality of service and cost of care but only has an impact on the length of stay at Linggajati Hospital with an R Square value (0.039) and Pvalue (0.000). Conclusions: The results of this research have implications for providing information to health workers to further optimize clinical pathway compliance and monitor quality control evaluation and hospital care costs.